Progression of C-reactive protein from birth through preadolescence varies by mode of delivery - Sitarik, Alexandra R.; Johnson, Christine C.; Levin, Albert M.; Lynch, Susan V.; Ownby, Dennis R.; Rundle, Andrew G.; Straughen, Jennifer K.; Wegienka, Ganesa; Woodcroft, Kimberley J.; Cassidy-Bushrow, Andrea E. (Frontiers in Pediatrics, 2023)
Introduction: Delivery via caesarean section (C-section) has been associated with an increased risk of childhood chronic diseases such as obesity and asthma, which may be due to underlying systemic inflammation. However, the impact of specific C-section types may be differential, as emergency C-sections typically involve partial labor and/or membrane rupture. Our objectives were to determine if mode of delivery associates with longitudinal profiles of high sensitivity CRP (hs-CRP) —a marker of systemic inflammation—from birth through preadolescence, and to examine if CRP mediates the association between mode of delivery and preadolescent body mass index (BMI). Methods: Data from the WHEALS birth cohort (N=1258) were analyzed; 564 of the 1258 children in the cohort had data available for analysis. Longitudinal plasma samples (birth through 10-years of age) from 564 children from were assayed for hs-CRP levels. Maternal medical records were abstracted to obtain mode of delivery. Growth mixture models (GMMs) were used to determine classes of hs-CRP trajectories. Poisson regression with robust error variance was used to calculate risk ratios (RRs). Results: Two hs-CRP trajectory classes were identified: class 1 (76% of children) was characterized by low hs-CRP, while class 2 (24% of children) was characterized by high and steadily increasing hs-CRP. In multivariable models, children delivered via planned C-section had 1.15 times higher risk of being in hs-CRP class 2, compared to vaginal deliveries (p=0.028), while no association was found for unplanned C-section deliveries [RR (95% CI)=0.96 (0.84, 1.09); p=0.49]. Further, the effect of planned C-section on BMI z-score at age 10 was significantly mediated by hs-CRP class (percent mediated=43.4%). Conclusions: These findings suggest potentially beneficial effects of experiencing partial or full labor, leading to a lower trajectory of systemic inflammation throughout childhood and decreased BMI during preadolescence. These findings may have implications for chronic disease development later in life.